Alcohol consumption by university students during the COVID-19 pandemic (Research, Society and Development, 2022)
This study aimed to verify the consumption of this psychoactive substance among students from two federal universities, in order to alert to the importance of promoting programs for the prevention of alcohol abuse and dependence in universities. 303 students from the universities UFPI and UFRA participated in the research. Data collection was obtained by completing an online questionnaire using the Google Forms platform. The results showed that 53% of the students surveyed already consumed alcoholic beverages before the pandemic. During the pandemic, 48% of students consumed alcohol once a week and 5% two to three times a week. As for the age at which the student consumed alcohol for the first time, 8% drank alcohol before the age of 14, 27% between 15 and 16 years old and 14% at 17 years old, that is, 49% of the researched university students drank alcohol for the first time when they did not have the legal minimum age for alcohol consumption. It is concluded that during the Covid-19 pandemic, the consumption of alcoholic beverages among university students was high, probably due to a set of factors such as anguish, loneliness, stress and lack of conviviality among students, caused by isolation and the social distancing imposed by health authorities. It is essential, on the part of educational institutions, to implement programs that monitor emotional and mental impairments in university students in pandemic and post-pandemic periods to promote improvements in the quality of life of these students.